Heavy metal removal of solid waste source sulphoaluminate cement with graphene oxide. (11th October 2021) - Yang, Fengming; Zhou, Xin; Pang, Fangjie; Wang, Weijie; Wang, Wenlong; Wang, Zengmei
Highlights: GO is the potential to promote the growth of ettringite crystals. Addition of GO can improve the ability of WSAC to immobilize heavy metals. The mechanism of solidification of heavy metals by WSAC and GO-WSAC was analyzed. Abstract: Heavy metal pollution is one of the most severe issues facing the environment for its persistent and stable physicochemical property. This research demonstrated that, ettringite crystal phase -- main hydration product of solid waste source sulphoaluminate cement (WSAC), has a highly efficient heavy metal removal via cation exchange. Meanwhile, due to large specific surface area, rich functional groups, good adsorption performance for heavy metals and ability to promote the growth of ettringite crystal, graphene oxide (GO) was selected to further improve the solidification effect of WSAC towards heavy metals. The heavy metal ion adsorption effects on the WSAC, including to theadsorbent dosage, solution pH, adsorption time, initial Cr(III) concentration, adsorption temperature, and competitive adsorption for multiple heavy metal ions, were systematically investigated. The experimental results revealed that with 0.03% GO addition, the compressive strength of WSAC after curing 1d, 3d, 28d increased by 24.1%, 18.6% and 21.5% compared to control sample, respectively, originating from promoting the hydration process and ettringite crystal growth in WSAC by GO. The heavy metal ion Cr(III)-exchanged by the Al(III) in ettringite crystal follows the Langmuir model with high exchange capacities, qm, 108.46 mg/g for GO-WSAC and 105.73 mg/g for WSAC. The GO-WSAC retains more excellent heavy metal ion removal capacity (95.2 mg/g, initial adsorbent dosage of 0.4 g) in very high concentration (400 mg/L), and the adsorption equilibrium could be reached basically within 10 min. When multiple ions coexist (Zn(II), Cu(II), Cr(III) and Cd(II)), WSAC and GO-WSAC still exhibit excellent removal efficiency, as high as 95.9% and 96.7%, respectively, apart from Cd(II) (only 75.03% and 89.3%, respectively). The findings in our research make WSAC as a new, environmentally friendly and cost-effective adsorbent for heavy metal ions removal from wastewater.